Status of medicinal plants in tropical forest of eastern Nepal - Gautam, Tilak Prasad (Nepalese Journal of Biosciences, 2013)
The present study deals with the medicinal properties of 24 species of plants belonging to 23 genera and 17 families found in tropical moist forest of Sunsari district, eastern Nepal. Among them, 5 species of medicinal plants are threatened according to the IUCN categories and Rauvolfia serpentina is included in the appendix II of CITIES.